Structural Aspects of Mixed Ligand Complexes of Ni(II) and Cu(II) Metal Chelates of Organic Acids with 1,10-Phenanthroline - Prakash, D.; Kumari, Asha; Kumari, Neetu (Asian Journal of Chemistry, 2012)
A series of mixed ligand complexes of the general formula ML2L' have been synthesized and characterized, where M = Ni(II) or Cu(II); L = deprotonated organic acids such as o-nitrophenol (ONP), 2,4-dinitrophenol (DNP), 2,4,6-trinitrophenol (TNP), 8-hydroxyquinoline (8HQ), 1-nitroso-2-napthol (1N2N) and o-aminobenzoic acid (OABA); L' = 1,10-phenanthroline. These complexes have been characterized by elemental analysis, molar conductance measurements, magnetic moment measurements, IR and electronic spectral analysis. The IR spectra suggest coordination of transition metal Ni(II) or Cu(II) with 1,10-phenanthroline through the nitrogen atoms of its pyridine fragments and N and/or O of the organic acid. The electronic spectral data and magnetic moment value suggest the octahedral geometry of the complexes.